Macs all in one for dummies - Hutsko, Joe , 1963-; Boyd, Barbara , 1929- (-- For dummies, 2012)
The ultimate beginner resource for learning the key features and tools of your Mac Macs are easy to use, but this guide helps you take advantage of all the cool features and make the most of your Mac. Fully updated, it covers the newest operating system, as well as the latest versions of iLife and iWork